I Am Hurt : Kunst als spiegel van de ziel. - Cornelisse, Eef; David, Astrid; Quaghebeur, Rolf (Gent : DAVID vzw, 2011)
Depelchin, Peter ; Anuwatwimon, Ruangsak ; Delrue, Ronny ; De Visscher, Tom ; De Wilde, Frederik ; Matei, Adi ; Spie, Merlin ; Van Imschoot, Jan ; Vleeschouwer, Kris ; Benhelima, Charif ; Bouckaert, Charlotte ; Cielen, Fia ; Graeffly, Rohan ; Coussement, Guilmot ; Lybeer, Charlotte ; Matthys, Michaël ; Bollansée, Marie Julia ; Boon, Elke Andreas ; Quint, Robert ; Scheurweghs, Julie ; Vandenberg, Philippe ; Vosters, Vadim
I Am Hurt. Kunst als spiegel van de ziel, Entrepot Fictief (Jan Colle vzw), Gent, 14/08/2011 - 10/09/2011
boek